5G low altitude network service and operation solutions - Qing ZHANG; Yi FENG; Dan MA; Qi LV (Dianxin kexue)
With the rapid development and maturity of civil UAV technology,the industry application puts forward higher and higher requirements for UAV data link.Using 5G network to provide data link for UAV and building the ground-air integration network can improve the service ability of UAV and enrich the service scenario.After analyz-ing the challenges faced by the traditional UAV data link,the 5G low altitude network solutions and service projects were proposed,while the 5G low altitude network operation solutions and 5G UAV application scenarios were ana-lyzed in the end.